Internet e letteratura: la fine di un idillio? (ENTHYMEMA, 2023)
The influence of new information technologies on creation and literary practice, as well as the evolutions and changes in the ways of communication and production of the works, lead to an analysis of the large laboratory which is the web and the relationship it has with literature. Today, after more than twenty years, this relationship seems to enter a more institutionalized phase, in which enthusiasm gives way to more prudent positions, even from integrated authors. For this reason, the purpose of this reflection is the analysis of the insight that some authors bring to the network and of the socio-cultural dynamics to which it gives life. Starting from the reflection by the collective Wu Ming on the blog Giap and examining Panorama by Tommaso Pincio and Anteprima Mondiale by Aldo Nove, we will try to grasp the transformations and to give light to the critics towards the network and its communication practices in contemporary society.
Keywords: Contemporary Literature; Internet; Social Network; Convergence; Wu Ming; Tommaso Pincio; Aldo Nove; Narrative Turn